2016
DOI: 10.1016/j.bpj.2016.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Pressure in Pancreatic Ductal Adenocarcinoma Is Dominated by a Gel-Fluid Phase

Abstract: Elevated interstitial fluid pressure can present a substantial barrier to drug delivery in solid tumors. This is particularly true of pancreatic ductal adenocarcinoma, a highly lethal disease characterized by a robust fibroinflammatory response, widespread vascular collapse, and hypoperfusion that together serve as primary mechanisms of treatment resistance. Free-fluid pressures, however, are relatively low in pancreatic ductal adenocarcinoma and cannot account for the vascular collapse. Indeed, we have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
137
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(150 citation statements)
references
References 68 publications
(103 reference statements)
13
137
0
Order By: Relevance
“…Cytokines recruit immune cells, which secrete extracellular matrix remodeling factors. Together these processes change the architecture of the organ creating a stiff fibrotic matrix, marked by increased interstitial pressure, which hinders the activity of the vascular system [1416]. Deregulated proliferation and growth factor release further influences blood vessel development, which is characterized by leaky vessels that inefficiently deliver nutrients and remove waste products of cellular metabolism, like lactate [17, 18].…”
Section: Features Of the Tumor Microenvironment That Affect Metabolismmentioning
confidence: 99%
“…Cytokines recruit immune cells, which secrete extracellular matrix remodeling factors. Together these processes change the architecture of the organ creating a stiff fibrotic matrix, marked by increased interstitial pressure, which hinders the activity of the vascular system [1416]. Deregulated proliferation and growth factor release further influences blood vessel development, which is characterized by leaky vessels that inefficiently deliver nutrients and remove waste products of cellular metabolism, like lactate [17, 18].…”
Section: Features Of the Tumor Microenvironment That Affect Metabolismmentioning
confidence: 99%
“…It has also been revealed that poor prognosis is associated with severe hypoxia in the primary tumor [14][15][16]. Moreover, the interstitial fluid pressure (IFP) has been reported to be elevated [17][18][19], and it has been suggested that highly elevated IFP together with a dense and extensive stroma may cause resistance to treatment by inhibiting the distribution of chemotherapeutic agents [19].…”
Section: Introductionmentioning
confidence: 99%
“…This remodeling of the microenvironment surrounding the cancer cells contributes to the elevation of the internal pressure in the cancerous tissue [9]. Moreover, in this process, the deposition of hyaluronan causes the compression of the intratumoral microvasculature and consequently prevents the drug from reaching the cancer cells [10]. In addition, hyaluronan works as a ligand for some receptors on the cell membrane and enhances the progression of cancer.…”
Section: Introductionmentioning
confidence: 99%